Multiscale Characterization of Joint Surface Roughness. Issue 12 (8th December 2017) - Nigon, Benoit; Englert, Andreas; Pascal, Christophe; Saintot, Aline
Abstract: Recent studies provided detailed characterizations of fault (i.e., shear fracture) roughness at different length scales. Similar investigation for joints (i.e., tensile fractures) are seldom and not as detailed. The present study aims at characterizing joint plumose patterns. We investigated the scale‐dependent surface roughness properties of S‐type plumoses. Joint surface measurements at relatively large scales were carried out with Light Detection and Ranging (LiDAR) technology. Joint surface measurements at the microscopic scale were carried out based on a noncontact optical method, using a Keyence VHX‐2000D microscope. Three parameters were used to characterize fracture surface elevation, standard deviation, Hurst exponent, and correlation length through 3 scale length orders of magnitude. Our study showed that standard deviation and correlation length decrease with scale, similarly to previous findings on faults. In addition, the range of Hurst exponents as a function of scale for the studied joint surface agrees well with those previously found for faults. However, directional analysis showed that correlation length and Hurst exponent of joint surfaces at scales smaller than 1 dm differ significantly from the ones of fault surfaces. In contrast to fault surface ornaments that are mainly characterized by linear structures, plumose structures show marked variability in orientation and anisotropy as a function of position on the joint surface. Key Points: LiDAR and digital microscope scans were conducted on one joint surface Plumose patterns were characterized by directional Hurst exponent and correlation length as a function of scale Compared to studies on fault, the anisotropic behavior changes as a function of scale and position